DETERMINING FACTORS RELATED TO THE TYPE OF CONTRACEPTIVES IN INDONESIA - Natya Ayu Candrika Ramania (Universitas Airlangga, 2020)
Family Planning Program is a government program designed as an effort to control population. The government initially recommends non-hormonal contraception, however in Indonesia, the use of non-hormonal contraception is less desirable by women of childbearing age. Most women of childbearing age in Indonesia prefer to use hormonal contraception. The study was conducted to determine the relationship between age, education, occupation, residential area, number of children alive, health insurance, husband’s support by determining the type of contraception in women of childbearing age in Indonesia. The study utilized secondary data obtained from the 2017 IDHS by using a cross-sectional design. The research sample is subjects who put the last type of contraception in a private midwivery and subjects who use implanted contraception, injections, pills, condoms, and IUD. The sample size in this study was 6,030 subjects. According to the study, several factors were found that showed a relationship with the determination of the type of contraceptives in Indonesia. These factors include age, level of education, employment status, residential area, number of children alive, and health insurance. However, the husband's support factor shows that it has no relationship with determining the type of contraceptives for women of childbearing age in Indonesia.